GIOTTO’S STIGMATIZATION OF SAINT FRANCIS: AN APPROACH FOR THE RECONSTRUCTION OF THE IMAGE - Lanfranchi, Maria Rosa (Protection of Cultural Heritage, 2019)
For the conservation restoration of Giotto’s Stigmatization, painted in the transept of Santa Croce, it was considered the possible new retouching of forms replaced by some old reconstruction, totally out of context after cleaning. The logical process followed in this specific case study was based on the drawing repetitions demonstrated by Giotto in his creations. The nature of the proposal of our of retouching it’s guaranteed by the reintegration technique that allows to recognize the new reconstructed forms and the reversible binder (watercolours) will allow a future cancellation of the fills.